Facilitated Polysulfide Redox Conversion by Delocalized Electrons in MBene Heterointerface for Highly Stable Lithium–Sulfur Batteries - Wu, Guifen; Fan, Yunmiao; Li, Jiatong; Shen, Zhaoxi; Xie, Yuxiu; Yang, Peixun; Pu, Jun (Nano-Micro Letters, 2026)
The shuttle effect of lithium polysulfides (LiPSs) and sluggish redox kinetics severely restrict the development of high-energy lithium–sulfur (Li–S) batteries. To alleviate this issue, this study adopts an in situ design strategy to construct tungsten carbide (WC) nanocrystals on the surface of two-dimensional (2D) tungsten boride (WB)-based MBene, creatively forming a WB@WC heterostructure to optimize the adsorption–migration–catalysis mechanism of LiPSs. The WB–WC heterointerface reduces the reaction energy barrier of LiPSs due to the electron delocalization effect and promotes the deposition/dissociation of Li2S and the transfer of charge. In situ Raman verified that WB@WC can effectively inhibit LiPSs shuttling. In situ X-ray absorption fine structure spectroscopy (XAFS) characterizations further explored the dynamic change of W valence state during LiPSs redox cycle. Encouragingly, the WB@WC-modified Li–S cell delivers an initial capacity of 1277 mAh g−1 at 0.2 C. It exhibits extremely stable cycling performance at 2 C, with a low-capacity decay rate of only 0.024% per cycle. Even under sulfur loading of 7.92 mg cm−2, high capacity of 7.9 mAh cm−2 can still be achieved. This work provides an effective method for regulating the activity of MBene-based catalysts. Highlights: 1 A multifunctional 2D tungsten boride (WB)@tungsten carbide (WC) heterostructure was innovatively fabricated by a fluorine-free MBene etching process and in situ carbonization technology. 2 The enhanced local electron delocalization effect at the heterointerface effectively suppressed the shuttle effect and improved the reaction kinetics, achieving an area capacity of up to 7.9 mAh cm−2 and a capacity attenuation as low as 0.024% per cycle. 3 In situ X-ray absorption spectroscopy verified the catalytic mechanism of WB-based MBene.